2021
DOI: 10.1021/acs.analchem.0c05174
|View full text |Cite
|
Sign up to set email alerts
|

Micropipet-Based Navigation in a Microvascular Model for Imaging Endothelial Cell Topography Using Scanning Ion Conductance Microscopy

Abstract: Scanning ion conductance microscopy (SICM) has enabled cell surface topography at a high resolution with low invasiveness. However, SICM has not been applied to the observation of cell surfaces in hydrogels, which can serve as scaffolds for three-dimensional cell culture. In this study, we applied SICM for imaging a cell surface in a microvascular lumen reconstructed in a hydrogel. To achieve this goal, we developed a micropipet navigation technique using ionic current to detect the position of a microvascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…We recently reported topographical images in an extracellular matrix-embedded vascular model using SICM under static culture conditions. [18] In this study, we showed that SICM is also applicable for shear-induced topographical analysis in MPS.…”
Section: Topographical Analysis Under Flow Stimulimentioning
confidence: 77%
See 2 more Smart Citations
“…We recently reported topographical images in an extracellular matrix-embedded vascular model using SICM under static culture conditions. [18] In this study, we showed that SICM is also applicable for shear-induced topographical analysis in MPS.…”
Section: Topographical Analysis Under Flow Stimulimentioning
confidence: 77%
“…[15] By combining SICM with SECM or other techniques, local chemical information of single cells [16] or cell membranes can be acquired at the nanoscale. [17] These topographical and functional evaluations using SPM are promising for the analysis of MPS, [18] and for SPM-compatible microfluidic devices, removable slabs, [19] ultrathin membranes, [20] and open-top microfluidic devices [18] were developed for the access of SPM into microfluidic devices. By combining these devices with atomic force microscopy (AFM), an analysis of the mechanical properties of circulating tumor cells [19b] and selective mRNA extraction from single cells [20] was realized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings could provide a basis to further understand the correlation between the dynamic reassembly of neurons and memory. Nashimoto et al reported an important application of nanopipette in revealing the topography of 3D cultured cell surface for the first time 26 (Figure 4B). They established a microvascular 3D-like models of endothelial cells, where microvascular lumen was reconstructed in a hydrogel.…”
Section: Nanopipette Applicationsmentioning
confidence: 99%
“…The detection mechanism is based on the increase in the electrical resistance of the pore in response to the excluded volume resulting from the introduced objects when applying electrical voltages. In scanning ion conductance microscopy, the ion conductance at a nanocapillary is used to measure the height of a sample [19,20]. In the present study, ion currents between channels separated by endothelial monolayers were monitored to evaluate their perfusion during vessel formation.…”
Section: Introductionmentioning
confidence: 99%